2012
DOI: 10.1002/marc.201100806
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Supramolecular Chirality in Co‐Assembled Polydiacetylene LB Films with Removable Azobenzene Derivatives

Abstract: Herein, we report a novel model that combines supramolecular chemistry and the LB technique for the chirality regulation of the PDA films. The helical packing of PCDA molecules and the chiroptical properties of the resulting PDA LB films can be easily modulated by different azobenzene derivatives. Moreover, the effect of the photo-isomerization of azobenzene chromophores on the helical formation of PCDA assemblies is investigated in detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…The CQO stretching vibration in pure PCDA samples appeared at 1693 cm À1 , which indicated that the carboxyl group was not in a free but an associated state. 19 Conversely, the carbonyl band in the HB complex shifted to 1703 cm À1 (as shown in Fig. 1b), lower than that of the free carboxylic acid, suggesting that the carbonyl group still interacted with a different H-bonding donor, presumably CH b of the triazole in TTB.…”
mentioning
confidence: 92%
“…The CQO stretching vibration in pure PCDA samples appeared at 1693 cm À1 , which indicated that the carboxyl group was not in a free but an associated state. 19 Conversely, the carbonyl band in the HB complex shifted to 1703 cm À1 (as shown in Fig. 1b), lower than that of the free carboxylic acid, suggesting that the carbonyl group still interacted with a different H-bonding donor, presumably CH b of the triazole in TTB.…”
mentioning
confidence: 92%
“…More prolonged irradiation resulted in a zero g CD value (750 s). This decrease is ascribed to the production of cis -azobenzene moieties with a bent structure, which prevents efficient trans -azobenzene stacks and leads to an ill-ordered structure. …”
Section: Resultsmentioning
confidence: 99%
“…The DA monomers 1 were polymerized after their self‐assembly resulted from the hydrogen bonding between amine and carbonyl groups (Scheme ) during the preparation of DA vesicles (see Experimental Section, Supporting Information) . There are many poly­merization methods for the preparation of PDAs, and the common approach is the UV‐induced photo‐polymerization .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the introduction of chiral structure into PDAs is helpful for the conjugated materials with some new properties, such as helical chirality, nonlinear response, and photo‐modulation. Thus, more and more people are attracted to the intensive research on the preparation of chiral PDAs as a challenge recently . Especially, chiral PDA films can be used as film sensors .…”
Section: Introductionmentioning
confidence: 99%